Development and Evaluation of an Optimized Energy Recovery System from Excess Heat of a Compressed Air System - Mañego, Andrew S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The aim of this study is to build a bounded optimized energy recovery system from the compressed air system’s excess heat. It is important to concentrate on the use of products that satisfy the requirements for performance and sustainability, as well as the need for energy that will be optimized. Purposive sampling is used to select the respondents, using quantitative research, specifically both descriptive and developmental methods. The researcher utilized a decision support tool developed by Kolaitis et al., (2020) as the primary research instrument of the study. The adopted tool was slightly modified to suit the assessment needs of the developed energy utilization system. All the main criteria components are interpreted as highly sustainable. The researcher utilized log sheets to determine the performance of the study. Finally, paired t-test was used to determine whether there was a significant difference in the performance of the study. The performance of the optimized energy after the implementation of the project was statistically higher than the performance of the optimized energy before the implementation of the project. The researcher concluded that the performance of the optimized energy recovery system from excess heat of a compressed air system after the installation and operation was effective and efficient based on the ratings of respondents and descriptive measures on the log sheet. For this kind of innovation, the manufacturing company with the same equipment should adopt and sustain it for potential energy savings and protect mother nature.